A study on cow welfare vis-Ã -vis sustainability of gaushalas (cow orphanages) - Singh, Ajmer; Kamboj, ML; Chandel, BS (Indian Journal of Dairy Science, 2022)
As soon as cows become uneconomic, they are abandoned. Since, gaushalas are considered to be best alternative to manage the ever increasing uneconomic and stray cattle population, it is important to study their sustainability levels vis-Ã -vis status of cow welfare level. The study finds that size and type of gaushala makes a difference wrt. sustainability indicators as well as welfare levels. The sustainability of Gaushalas could be increased by increasing their sources of income and catering to social needs, besides organizing professional trainings. The cow welfare level in these gaushalas was found to be traversing in harmony with their sustainability levels.